Conservative management in an elderly woman with proximal humeral head fracture and massive rotator cuff tear who refused surgery: A case report. Issue 4 (October 2020) - Brindisino, Fabrizio; Maselli, Filippo; Giovannico, Giuseppe; Dunning, James; Mourad, Firas
Abstract: Background: Proximal humerus fractures (PHFs) account for between 4% and 10% of all fractures in the elderly people and osteoporosis is frequently related to PHF. Furthermore, rotator cuff (RC) tears are also extremely common, affecting at least 10% of people aged over 60 in the United States. Among shoulder pathologies, the periarticular soft tissue disorders, including the RC, this is considered to be the most common. The incidence of full thickness RC tears increases with age. An aggressive surgical approach is often required for patients with massive RC tear and PHFs to restore the patients' functional daily living activities. To the best of the authors' knowledge, this is the first case report describing a successful conservative management in an elderly patient with a full thickness RC tear and PHF that refused surgery. Case description: This report describes the case of a 90-year-old woman with a massive RC tear who fell over on the sidewalk and sustained a PHF. The patient refused surgery even though it was recommended and prescribed by an orthopaedic surgeon. Intervention: After having her shoulder immobilized with a brace as prescribed by the orthopaedic physician, the patient began a shoulder rehabilitation program with progressive work load exposure, functional movements and a pain and kinesiophobia education program. Outcomes: After 3 and a half months, the patient achieved full recovery to her pre-injury level of function. Such outcome was assessed using the Numeric Pain Rating Scale (NPRS), the Disability of the Arm, Shoulder and Hand (DASH) scale, the Fear-Avoidance Beliefs Questionnaire (FABQ), the Pain Catastrophysing Scale (PCS), and the Global Rating of Change (GROC) scale. Discussion and conclusion: In an elderly patient with a massive RC tear and an undisplaced PHFs, patient education, pain reconceptualization and change of beliefs in combination with progressive work load exposure appeared to be an effective management strategy to achieve a return to the pre-injury level of function.